Islam and Ideology in Online Media Headlines: A Critical Discourse Analysis of Trans7’s Pesantren Representation - Vini Rizki Nurodiah; Putri Azzahra Henda Puspitasari; Raden Viranty Kamilatul Fasa; Sajidin Sajidin; Dody S. Truna; Erni Haryanti; Hapid Ali (KEDJATI Journal of Islamic Civilization, 2025)
This study examines the construction of Islam and ideology in online media headlines representing the Lirboyo Pesantren following the broadcast of Trans7's Xpose Uncensored using Fairclough's (1995) three-dimensional Critical Discourse Analysis (CDA) framework. Through this theory, it is intended to explore how online media headlines shape the construction of Islam, Ideology, Pesantren, and religious authority in Indonesia's digital public sphere. Using a descriptive qualitative approach, 30 news headlines were analyzed across three dimensions of CDA: textual (linguistic and evaluative framing), discursive (the production and circulation of institutional meaning), and socio-cultural (the relationship among ideology, power, and Islamic ethics). The results show that religious lexicons such as "sowan" (visit), "maafkan" (to forgive), and "bersholawat" (blessings, prayers, or salutations sent upon the Prophet Muhammad) are strategically employed to represent Islam as an ethical and communicative ideology. At the level of discursive practice, the media negotiates moral legitimacy by adopting Pesantren values, ​​such as "amanah" (honesty) and "'adil" (justice). Meanwhile, at the socio-cultural level, Islam functions as a counter-hegemonic moral force that balances the logic of media capitalism with spiritual authority. These findings suggest that media discourse not only reflects reality but also reconstructs Islamic moral authority through language and institutional negotiations. This study concludes that Islamic authority in the digital era has transformed into a mediated moral force. Hence, this research contributes to the study of Islamic communication and media by integrating CDA and Islamic ethical principles to explain the role of Islam as a discourse and ideology in shaping contemporary public morality.